PENGARUH BIAYA PRODUKSI DAN HARGA JUAL TANDAN BUAH SEGAR (TBS) KELAPA SAWIT TERHADAP PENDAPATAN PETANI DI KUD LINGKUNG AUR II KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT - Syanti, Syanti; Yulihardi, Yulihardi; Amaluis, Dina (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study examines the factors that influence the Farmers Income in KUD LingkungAur II Pasaman District of West Pasaman " . The variables of this study is the Cost of Production (X1 ) and the Sale Price of Fresh Fruit Bunches ( X2 ) as independent variables and Farmer Income ( Y ) as the dependent variable .The type of research is usedÂ  a quantitative approach by Â using time series data of 2011-2012 in the form of monthly data obtained directly from KUD LingkungAur II Pasaman District of West Pasaman . Data analysis tools are Ekometrika approachby Â using multiple regression equation in the form of Double Log.The result of study found that in partial cost of production is significant influence toward the Farmersâ Income by Î± = 10 % , while the variable selling price partially is significant effect on Farmers Income with Î± = 5 % . Simultaneously, the variable cost of production and selling price are significant influence toward FarmersâIncome .From the results of the study is suggested that further strengthen the network of cooperatives and market information in order to determine the price that can increase farmers income.